Perceptions of Scratch Programming among Secondary School Students in KwaZulu-Natal, South Africa - Mudaray Marimuthu; Predhayen Govender (The African Journal of Information and Communication, 2018)
Scratch programming was designed with the aim of helping students to develop their logical thinking skills as well as enhancing their problem-solving capabilities, without having the technical distractions associated with more advanced programming languages such as Java. This study, guided by the technology acceptance model (TAM), focused on exploring the associations between perceived usefulness, perceived ease of use, attitude towards use, and behavioural intention to use the Scratch programming language, with the aim of identifying how Scratch programming was perceived by a group of South African students in Grades 10 and 11 at two high schools. Results indicated, among other things, that Grade 10 students perceived Scratch to be easy to use and useful, and Grade 11 students found it to be easy to use but useful only in learning introductory programming concepts. These and other findings suggest that while Scratch helps students understand logic and problem-solving, it does not assist sufficiently in preparing them for using a higher-level programming language such as Java. The article concludes with recommendations for South African education policymakers, including proposals that a bridging programming language be introduced between Scratch and Java, and that Scratch be introduced much earlier than in Grade 10.